Denaturation-Enhanced Droplet Digital PCR for Liquid Biopsies. (4th January 2020) - Fitarelli-Kiehl, Mariana; Yu, Fangyan; Ashtaputre, Ravina; Leong, Ka Wai; Ladas, Ioannis; Supplee, Julianna; Paweletz, Cloud; Mitra, Devarati; Schoenfeld, Jonathan D; Parangi, Sareh; Makrigiorgos, G Mike
Abstract: BACKGROUND: Although interest in droplet-digital PCR technology (ddPCR) for cell-free circulating DNA (cfDNA) analysis is burgeoning, the technology is compromised by subsampling errors and the few clinical targets that can be analyzed from limited input DNA. The paucity of starting material acts as a "glass ceiling" in liquid biopsies because, irrespective how analytically sensitive ddPCR techniques are, detection limits cannot be improved past DNA input limitations. METHODS: We applied denaturation-enhanced ddPCR (dddPCR) using fragmented genomic DNA (gDNA) with defined mutations. We then tested dddPCR on cfDNA from volunteers and patients with cancer for commonly-used mutations. gDNA and cfDNA were tested with and without end repair before denaturation and digital PCR. RESULTS: By applying complete denaturation of double-stranded DNA before ddPCR droplet formation the number of positive droplets increased. dddPCR using gDNA resulted in a 1.9–2.0-fold increase in data-positive droplets, whereas dddPCR applied on highly-fragmented cfDNA resulted in a 1.6–1.7-fold increase. End repair of cfDNA before denaturation enabled cfDNA to display a 1.9–2.0-fold increase in data-positive signals, similar to gDNA. Doubling of data-positive droplets doubled the number of potential ddPCR assays that could be conducted from a given DNA input and improved ddPCR precision for cfDNA mutation detection. CONCLUSIONS: dddPCR is a simple and useful modification in ddPCR that enables extraction of more information from low-input clinical samples with minor change in protocols. It should be applicable to all ddPCR platforms for mutation detection and, potentially, for gene copy-number analysis in cancer and prenatal screening.